Investigation of the Transport Pathways Associated with Enhanced Brain Delivery of Peptide Drugs by Intranasal Coadministration with Penetratin - Noriyasu Kamei (MDPI AG, 2021)
We previously found that coadministering peptides and proteins with the cell-penetrating peptide L-penetratin intranasally significantly increased transport to the brain and enhanced pharmacological effects. The present study aimed to clarify the mechanisms of nose-to-brain drug delivery enhancement by L-penetratin coadministration. First, we compared the concentrations of Exendin-4 in plasma and brain after intranasal and subcutaneous administration and suggested that coadministration with L-penetratin facilitated the direct nose-to-brain transport of Exendin-4. Second, we demonstrated that L-penetratin did not stimulate the transport of Cy7-labeled Exendin-4 and insulin through the trigeminal nerves but shifted their distribution to the olfactory mucosal pathway. Third, we investigated the distribution of insulin into the deeper regions of the brain after delivery via the olfactory pathway and suggested that insulin had entered the olfactory bulb, bottom part of the brain, and perivascular space through the cerebrospinal fluid and had diffused throughout the brain. We further demonstrated that intranasally delivered insulin with L-penetratin specifically accumulated on the hippocampus neuronal cells. Thus, this study suggested that administrating peptide drugs intranasally with L-penetratin allows direct transport to the olfactory bulb, bottom part of the brain, and perivascular space of the cerebral artery. This technique also potentially allows targeting of specific brain areas.